Pembelajaran Bermakna Melaui Implementasi Kerangka UBD Berpendekatan Tarl dalam Mengakomodasi Karakteristik Peserta Didik Sekolah Dasar - Nuryatul Afifah; Veryliana Purnamasari; Ri’ah Nurhayati (Journal on Education, 2025)
This study aims to analyze the implementation of the UbD framework integrated with the TaRL approach in creating meaningful learning in Elementary Schools. The study was conducted with a qualitative approach through a case study method at SDN Sarirejo, East Semarang, Central Java. The study was conducted during October 2024 at SDN Sarirejo in general and class 3C with 25 students in particular. Data collection was carried out through in-depth interviews, observations, and document analysis. The results of the study indicate that the UbD framework provides a learning structure that focuses on long-term goals, authentic assessments, and learning planning, while the TaRL approach ensures that learning is adjusted to the level of student ability. This combination creates an inclusive, learner-centered learning environment that is effective in increasing student engagement and understanding. Observations also show that the integration of these two approaches has succeeded in improving students' collaboration skills and learning motivation through problem-based learning methods that are relevant to everyday life. This study recommends the implementation of UbD and TaRL simultaneously to improve the quality of learning according to the needs and characteristics of students